Awareness, attitudes, and barriers toward Transthyretin Amyloid Cardiomyopathy in Latin America: A questionnaire-based cross-sectional study - Cecilia Camacho-Hubner; Marcia Waddington-Cruz; María Juliana Rodríguez-González; Marcus Vinicius Simões; Juan David López-Ponce de León; Fabio Fernandes; Erika María Martínez-Carreño; Juan Pablo Costabel; Enrique A. Berrios-Bárcenas; Fabio Barroso; José Angel Cigarroa López; Rosa Ortega Reyes; et al. (PLoS ONE, 2026)
Background Cardiac Amyloidosis (CA), specifically Transthyretin Amyloid Cardiomyopathy (ATTR-CM), is an under-recognized, progressive, and fatal disease. Comprehensive primary data describing awareness, attitudes, and barriers to treatment in Latin America (LATAM) are lacking, highlighting a gap between guidelines and real-world clinical practice. Methods A cross-sectional, questionnaire-based observational study was conducted among 470 physicians actively involved in patient management across 8 LATAM countries (June-August 2023). The study assessed their awareness, attitudes, and barriers concerning ATTR-CM. Descriptive analysis was performed. Results Limited knowledge of ATTR-CM was observed. Awareness of its pathophysiology was reported by 50.2%. Patients consulted 4–5 physicians before receiving a confirmed diagnosis. Cardiologists managed most day-to-day cases (76.2%). Transthyretin genetic testing was available to only 26.4%. Local treatment protocols relied on international guidelines (87.4%), with Real-World Data considered important by 60.6%. Patient cost and access to tafamidis were frequently reported barriers. Follow-up commonly relied on echocardiography, NT-pro BNP, NYHA classification, and ECG/Holter ECG. Conclusions Difficulties in ATTR-CM diagnosis and management in LATAM were influenced by varying knowledge levels, gaps in diagnostic algorithms, and significant access barriers. These factors contribute to delayed diagnosis and management. Enhanced, tailored training strategies and collaborative efforts are necessary to improve early diagnosis, effective treatment, and ultimately, patient outcomes in the region.